Self-sustaining closed-loop multienzyme mediated conversion of amines into alcohols in continuous reactions - Contente, Martina L.; Paradisi, Francesca (Nature Publishing Group, 2018)
The synthesis of alcohols from amines starting material is an excellent, yet challenging, strategy for the preparation of pharmaceuticals and polymers. Here, we developed a versatile, self-sustaining closed-loop multienzymatic platform for the biocatalytic synthesis of a large range of non-commercially available products in continuous flow with excellent yields (80>99%), reaction times and optical purity of secondary alcohols (>99 e.e.). This process was also extended to the conversion of biogenic amines into high value alcohols, such as the powerful anti-oxidant hydroxytyrosol, and the synthesis of enantiopure 2-arylpropanols via dynamic kinetic resolution of commercially affordable racemic amines. The system exploits the in situ immobilisation of transaminases and redox enzymes which were combined to cater for a fully automated, ultra-efficient synthetic platform with cofactor recycling, in-line recovery of benign by-products and recirculation of the aqueous media containing the recycled cofactors in catalytic amount, which increases the efficiency of the system by over 20-fold.